Implementasi Program Tahsin Dengan Metode Usmani Di Masjid Al-Ikhlas Sambilegi Lor - Herman, Riki; Muhammad Rizki (Al-Khazin: Jurnal Pendidikan Agama Islam, 2025)
Tahsin Program with the Usmani Method of Al-Ikhlas Mosque Sambilegi-Lor Maguwoharjo Depok Sleman Yogyakarta, Reading the Qur'an correctly as revealed is the obligation of every Muslim and Muslim woman, but the ability of the majority of Muslims is still concerning, this can be seen from the low level of public engagement with the Qur'an and many factors that cause this situation, including teaching methods that are less manhaji, inadequate teachers or less aware individuals weakness in the Tajwidul Qur'an so that we are not interested in teaching, whatever the obvious reason we still believe in the wisdom of Allah "And indeed We have made the Qur'an easy to learn." Therefore, many methods of learning the Qur'an have emerged to answer the challenges faced by Muslims, especially in the ability to read the Qur'an. Therefore, the publication of the Ottoman Method seems to continue the dream of previous scholars to improve the quality of reading the Qur'an, because the Ottoman Method is believed to improve the ability to read the Qur'an properly and correctly. This study aims to: (1) How to Implement the Tahsin Program with the Usmani Method of the Al-Ikhlas Sambilegi-Lor Mosque of Maguwoharjo Depok Sleman Yogyakarta (2) What are the obstacles to the implementation of the Tahsin Program with the Usmani method of the Al-Ikhlas Sambilegi-Lor Mosque of Maguwoharjo Depok Sleman Yogyakarta. (3) What is the contribution of the implementation of the tahsin program with the Usmani method of the Al-Ikhlas Sambilegi-Lor Mosque Maguwoharjo Depok Sleman Yogyakarta. This research is a qualitative research with a case study method. Data collection was carried out using interviews, observations and documentation. The data analysis used is a model owned by Miles and Huberman which consists of three analysis components, in the form of: data reduction, data presentation and conclusion drawn. The results of this study are: (1) Implementation of the Tahsin Program with the Usmani Method of the Al-Ikhlas Mosque Sambilegi-Lor Maguwoharjo Depok Sleman Yogyakarta using the talaqi technique (2) Obstacles to the Implementation of the Tahsin Program with the Usmani Method of the Al-Ikhlas Mosque Sambilegi-Lor Maguwoharjo Depok Sleman Yogyakarta: Difficulties in reading hijaiyah letters with the correct Makharij al-ḥuruf because they are carried away by the readings brought as children, Insufficient time makes learning ineffective,  and the age factor because many of the worshippers of the Al-Ikhlas mosque are elderly. (3) What is the contribution of the implementation of the tahsin program with the Usmani method of the Al-Ikhlas Sambilegi-Lor Mosque Maguwoharjo Depok Sleman Yogyakarta; The congregation can read the verses in the Qur'an with a clearer sound of his Makharij al-ḥuruf. It can help the congregation learn the Qur'an, as well as being able to teach it to people who need it as early as possible.